Development of whey protein concentrate/pullulan composite films containing bacteriophage A511: Functional properties and anti-Listerial effects during storage. (September 2022) - Kamali, Sara; Yavarmanesh, Masoud; Habibi Najafi, Mohammad B.; Koocheki, Arash
Abstract: The present research examined the stabilization of Listeria phage A511 in whey protein concentrate (WPC), pullulan (PULL) films and their composites. The functional properties of the films were investigated during 60 days of storage at 25 °C and relative humidity of 53%. Pure films of WPC and PULL were not successful in phage stabilization. The highest phage recovery at zero time belonged to 30WPC:70PULL and 50WPC:50PULL films. Phage distribution was uniform in composite films. Addition of phage to the films resulted in enhanced opacity, b and ∆E. Antimicrobial effects in the solid medium in 50WPC:50PULL and 70WPC:30PULL films were reduced to zero, and the opacity, b and ∆E of phage-containing films increased over 60 days. In 30WPC:70PULL film the elastic modulus and tensile strength were enhanced while the elongation at break was reduced over time. Overall, 30WPC: 70PULL film had the best performance of the physical, mechanical and anti- Listerial properties during storage. Graphical Abstract: ga1 Highlights: The highest phage recovery at zero time belonged to 30WPC:70PULL & 50WPC:50PULL films. Three composite films could maintain phage titers for 20 days. After 60 days, most of the phages were recovered from 30WPC:70PULL film. The inhibitory zone reached zero after 60 days in 70WPC: 30PULL and 50WPC:50PULL films. The visual properties changed in all films over 60 days of storage.